Сухово-Кобылин: роман / Наталья Старосельская - Старосельская Наталья Давидовна (Жизнь замечательных людей, 2003)
Экземпляры: (20.12.07г.) / Инвентарный номер: 44185 / Цена: 94.93 / Сис.шифр: 83.3 / Авт.знак: С77 / ББК: 83.3